Development of a boost-inverter converter under electromagnetic compatibility stress equipping a photovoltaic generator - Bechekir, Seyfeddine; Zeghoudi, Abdelhakim; Ould-Abdeslam, Djaffar; Brahami, Mostefa; Slimani, Helima; Bendaoud, Abdelber (Національний технічний університет "Харківський політехнічний інститут", 2023)
Introduction. Static converters are among the most widely used equipment in several applications, for example, electric power transmission, motor speed variation, photovoltaic panels, which constitute the electronic components. The design of a power electronics device is done without any real means of predicting electromagnetic disturbances during the product development phase. This case-by-case development process is repeated until a solution is found that best respects all the electromagnetic compatibility constraints. The purpose is the development of a boost-inverter converter under electromagnetic compatibility constraints. The improvements made to the inverter are mainly in the control, the choice of power switches and the electromagnetic compatibility solutions brought to the device. The quality of the wave is improved by acting on the type of control and the choice of switches. Methods. In the first time, we have highlighted a comparison between two most frequently used power components (MOSFET and IGBT) in the inverter and the boost by simulation using ISIS and LT-spice softwares. The sinusoidal voltage with modulation circuit is greatly simplified by the use of the PIC16F876A microcontroller. In a second step, we validate the obtained results with experimental measurements. We start with the boost, then the inverter. In addition, the circuits made are housed in boxes to avoid accidental contact for people. The equipment is designed to isolate the load from the power supply in case of: over voltages, under voltages, high and low battery level and short circuits. Results. All the simulations were performed using the ISIS and LT-spice softwares. The obtained results are validated by experimental measurements performed in the ICEPS Laboratory at the University of Sidi Bel-Abbes in Algeria. The realization of a single-phase inverter with a pulse width modulation control, associated with a boost chopper and the waveforms of the current and voltage across each static converter its opening are presented. The sources of disturbances in power devices are at the origin of the temporal and frequency characteristics of the signals coming from the hot spots of the power switches and the resonances created during the switching of these elements.

Статичні перетворювачі відносяться до обладнання, що найбільш широко використовується в декількох застосуваннях, наприклад, для передачі електроенергії, зміни швидкості двигуна, у фотогальванічних панелях, які складають електронні компоненти. Проєкт устрою силової електроніки виконується без будь-яких реальних засобів прогнозування електромагнітних перешкод на етапі розробки продукту. Цей процес індивідуальної розробки повторюється доти, доки знайдено рішення, яке найкраще враховує всі обмеження електромагнітної сумісності. Метою є розробка підвищувально- інверторного перетворювача при обмеженнях за електромагнітною сумісністю. Удосконалення, внесені в інвертор, в основному стосуються управління, вибору силових вимикачів та рішень щодо електромагнітної сумісності, реалізованих у пристрої. Якість хвилі покращується за рахунок впливу на тип керування та вибір перемикачів. Методи. Вперше ми підкреслили порівняння між двома найбільш часто використовуваними силовими компонентами (MOSFET та IGBT) в інверторі та підвищенням шляхом моделювання з використанням програмного забезпечення ISIS та LT-spice. Синусоїдальна напруга зі схемою модуляціїзначно спрощується за рахунок використання мікроконтролера PIC16F876A. На другому етапі ми підтверджуємо отримані результати експериментальними вимірами. Починаємо з Boost, потім з інвертора. Крім того, виготовлені схеми розміщені в коробках, щоб уникнути випадкового дотику людей. Устаткування призначене для відключення навантаження від джерела живлення у разі: перенапруги, зниженої напруги, високого та низького рівня заряду батареї та короткого замикання. Результати. Усі розрахунки проводилися з використанням програм ISIS та LT-spice. Отримані результати підтверджені експериментальними вимірами, проведеними в лабораторії ICEPS Університету Сіді-Бель-Аббес в Алжирі. Представлено реалізацію однофазного інвертора з керуванням на базі широтно-імпульсної модуляції, пов'язаного з підвищуючим переривником, а також осцилограми струму та напруги на кожному відкритті його статичного перетворювача. Джерелами збурень у силових пристроях є часові та частотні характеристики сигналів, що надходять з гарячих точок силових ключів, та резонанси, що створюються при комутаціїцих елементів.
Keywords: inverter; converter; microcontroller; electromagnetic compatibility; інвертор; перетворювач; мікроконтролер; електромагнітна сумісність